Presentation - Waldomiro José Silva Filho; Marcos Antonio Alves (Trans/Form/Ação)
It is with great happiness and honor that we present this special issue of Trans/Form/Ação: Unesp journal of philosophy in honor of Ernest Sosa. One of the most influential voices in the contemporary philosophy, Ernest Sosa was born in Cárdenas, Cuba, on June 17, 1940. He earned his Bachelor of Arts (B.A.) and Master of Arts (M.A.) from the University of Miami and his Doctor of Philosophy (Ph.D.) from the University of Pittsburgh in 1964. Since 2007, he has been Board of Governors Professor of Philosophy at Rutgers University.